Self-aggregation propensity of the Tat peptide revealed by UV-Vis, NMR and MD analyses. Issue 35 (24th August 2017) - Macchi, Sara; Nifosì, Riccardo; Signore, Giovanni; Di Pietro, Sebastiano; Boccardi, Claudia; D'Autilia, Francesca; Beltram, Fabio; Cardarelli, Francesco
Abstract : The self-aggregation propensity of unlabeled and TAMRA-labeled Tat11 peptides has been revealed for the first time by UV-Vis, NMR and MD analyses. Abstract : By a combination of UV-Vis analyses, NMR-based diffusion measurements and MD simulations we have demonstrated for the first time that the HIV-1 Tat arginine-rich peptide (Tat11 ) is able to self-aggregate in both its fluorescently labeled and unlabeled variants. We propose Tat11 dimerization as the dominant aggregation process and show that the associated equilibrium constant increases ten-fold by labeling with the standard TAMRA dye. Also, we extend similar conclusions to other cationic cell penetrating peptides (CPPs), such as Antennapedia (Ant) and nona-arginine (R9).